POLA HIDUP KONSUMTIF DI KALANGAN MAHASISWI STUDI KASUS MAHASISWI STKIP PGRI SUMATERA BARAT PROGRAM STUDI PENDIDIKAN SOSIOLOGI ANGKATAN 2012 - Afrida, Nengki; Fitlayeni, Rinel; Prahara, Surya (Pendidikan Sosiologi, 2013)
The research was motivated by the basic assumptions about student consumptive lifestyle STKIP PGRI West Sumatra Sociology Program class of 2012, related to the reality on the ground is known that the student consumptive lifestyle is an expression to be recognized by the environment as a result they feel compelled to dress as perfect as possible. Clothes which they use not indicated or reflects an educator, therefore the problem can be formulated as follows: how consumptive lifestyle in West Sumatra student PGRI STKIP Sociology Program Force 2012.The theory used in this study is a consumerist society by Jeand Baudrillard. This type of research is qualitative research. Informants in this study is a student of Sociology of Education Studies Program 2012 Force of nine people, the selection of informants using purposive sampling technique. Data used in this study is primary data and secondary data. Method of data collection is done in two ways: (1) observation (non-participant observer), (2) in-depth interviews. Analysis of the data used by the model of qualitative research methodology Miles and Huberman, namely: (1) data collection phase, (2) data reduction phase, (3) the stage presentation of data, (4) the conclusion stage.It can be concluded that the reason for living consumptive student is (1) make it look attractive, as one student education candidates are expected to appear as attractive as possible. (2) more confident, buy nice clothes and branded can boost their confidence. (3) Following the trend, the student showed it to others to see and imitate the style of clothing is used, (4) feeling different from others, in terms of showing that they want to look different from the other student. Student consumptive lifestyles can be seen from (1) the criteria in selecting the types of goods are more likely to dress Chiffon, Longdrees, Logo, Levis, Jean s, and a bag with the brand Prada, Furla, Shopie Martin, as well as wearing the hijab Pasmina, (2) Frequency of shopping, (3) Location spending usually visit the Plaza Andalas, Basko and Boutique, (4) Costs incurred for expenditure, the average Rp.800.000 - Rp.500.000Â usually one time role in the purchase of goods a month.